1989
DOI: 10.1139/b89-225
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of white mold (Sclerotinia sclerotiorum) of bean by fungi from bean and rapeseed flowers

Abstract: 1989. Antagonism of white mold (Sclerotinia sclerotiorum) of bean by fungi from bean and rapeseed flowers. Can. J. Bot. 67: 1775-1781. Filamentous fungi from white bean and rapeseed flowers were isolated, characterized, and evaluated for potential as antagonists to Sclerotinia sclerotiorum (Lib.) de Bary. Various fungi were isolated from surface-sterilized petals sampled from four developmental stages ranging from freshly opened flowers to petals that had lodged on plant surfaces. Alternaria and Cladosporium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Thebehaviour of E. purpurascens may be attributable to its ecological competence or to a different mechanism of biocontrol action, such as antibiosis, which might be independent of the atmospheric environment. Studies of the mechanism(s) of action of this B CA have reported that both competition and antibiosis may be important in disease suppression [Boland and Hunter, 1988;Boland and Inglis, 1989;Mercier and Reeleder, 1987;Zhou and Reeleder, 1990;Zhou etal., 1991].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thebehaviour of E. purpurascens may be attributable to its ecological competence or to a different mechanism of biocontrol action, such as antibiosis, which might be independent of the atmospheric environment. Studies of the mechanism(s) of action of this B CA have reported that both competition and antibiosis may be important in disease suppression [Boland and Hunter, 1988;Boland and Inglis, 1989;Mercier and Reeleder, 1987;Zhou and Reeleder, 1990;Zhou etal., 1991].…”
Section: Discussionmentioning
confidence: 99%
“…After plants had started flowering (3-4 wk), bean petals at stages A (attached, recently opened flowers) and B (attached flowers that had started to wilt or senesce) [Boland and Inglis, 1989] were collected daily until flowering ceased. The petals were sterilized using propylene oxide according to Inglis [1989]. Aliquots of 2 ml propylene oxide at 4 ~ were pipetted into desiccation chambers where the petals were arranged in single layers on a perforated screen.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations